Study Literatur: Kacang Kedelai sebagai Obat Herbal Indonesia Penurun Kadar Kolesterol - Risky Andre ansyah (Herbal Medicine Journal, 2023)
The level of cholesterol in the body is so high that it negatively affects a sick person. Without effective treatment, the possible negative effects on the body, such as strokes and heart attacks, can even cause death. Excess cholesterol in the body can accumulate on the walls of the arteries and cause blockage of blood flow which should flow properly through body anatomy examples are brain and heart. Based on the results of research that has been carried out, There are many natural herbal medicines to minimize hypercholesterolemia including soy. This natural herbal remedy is used as an alternative treatment, so you don't always have to rely on prescription drugs. The method applied to write this article is to use a literature review approach. The journal unification process is carried out by selecting research journals based on predetermined criteria. The criteria used are:Journals indexed by Google Scholar published within the last six (6) years. Based on the results of this research, it can be concluded that natural herbal products from Indonesia, namely soybeans, can be used as an alternative choice for patients with hypercholesterolemia, but must use a certain dose.